Sub-200-kHz single soliton generation in a long ring Er-fiber laser with strict polarization control by using twisted fiber. (June 2020) - Rodríguez-Morales, L.A.; Ibarra-Escamilla, B.; Armas-Rivera, I.; Pottiez, O.; Andrés, M.V.; Durán-Sánchez, M.; Kuzin, E.A.
Highlights: The regimes of mode-locking operation depend on the initial polarization state. A novel way to solve the overdriven nonlinear effects is reported. Single-solitons with low repetition rate have potential biomedical applications. To the best of our knowledge it is the longest single-solitons cavity ever reported. Abstract: In the present work we demonstrate a novel single-soliton ultra-low pulse repetition frequency passively mode-locked erbium-doped fiber laser. We mitigate the residual linear birefringence of fiber by fiber twist to achieve a strict control of polarization. For mode-locking the nonlinear polarization rotation (NPR) was used. Special technique was applied to reduce the overdriving of NPR that allows the generation of single soliton in ultra-long cavity. The strict control of polarization yields a stable relation between the polarization state of the pulses propagating in the cavity and the regimes of generation. A 192.12-kHz train of soliton pulses was obtained with pulse duration of 4.7 ps at 1560.1 nm, the average power was 29 μW and the estimated peak power was ̴ 30.8 W with an energy of 150.9 pJ.